Generalized Jordan triple (ζ, ξ)-derivations on semiprime rings - Abu Zaid Ansari; Faiza Shujat; Muzibur Mozumder; Wasim Ahmed (Journal of Mahani Mathematical Research)
The purpose of this research is to demonstrate the following assertions: an additive mapping $\mathcal{H}$ is a generalized ($ζ, ξ$)-derivation associated with a ($ζ, ξ$)-derivation ${\bf h}$, where $ζ, ξ$ are endomorphisms on a $(m+n+p-1)!$-torsion free semiprime ring $\mathcal{A}$. Here we prove another result in the setting of the generalized left ($ζ, ξ$)-derivation on $\mathcal{A}$.